Green synthetic route to antimalarial and antibacterial agent CJ-15,801 and its isomer cis-CJ-15,801 - Kashinath, K.; Swaroop, Pandrangi Siva; Reddy, D. Srinivasa (RSC Advances, 2012)
An efficient and rapid synthesis of antiplasmodial and antibacterial agent CJ-15,801 and its isomer cis-CJ-15,801 is disclosed. We have made an attempt towards ``Ideal Synthesis'' or a step towards ``Dial-a-Molecule'' by reducing the number of steps, following atom economy, and a green synthetic route.